Technology, Transactions Costs, and Investor Welfare: Is a Motley Fool Born Every Minute? - Lynn A. Stout (Washington University Law Quarterly, 1997)
Computer network technology promises to revolutionize the secondary securities market and particularly to reduce dramatically the marginal costs associated with trading corporate equities. Lowering transactions costs usually is presumed to increase trader welfare. Certain unique characteristics of the secondary securities market suggest, however, that reducing the marginal costs associated with trading stocks may have the perverse and counterintuitive effect of decreasing investor welfare. Policymakers should consider this possibility as they respond to the market's rapid evolution.
Keywords: Electronic trading of securities